2009
DOI: 10.1088/0004-6256/137/5/4160
|View full text |Cite
|
Sign up to set email alerts
|

SWIFTX-RAY AND ULTRAVIOLET MONITORING OF THE CLASSICAL NOVA V458 VUL (NOVA VUL 2007)

Abstract: We describe the highly variable X-ray and UV emission of V458 Vul (Nova Vul 2007), observed by Swift between 1 and 422 days after outburst. Initially bright only in the UV, V458 Vul became a variable hard X-ray source due to optically thin thermal emission at kT = 0.64 keV with an X-ray band unabsorbed luminosity of 2.3 × 10 34 erg s −1 during days 71-140. The X-ray spectrum at this time requires a low Fe abundance (0.2 +0.3 −0.1 solar), consistent with a Suzaku measurement around the same time. On day 315 we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…2b) might point towards intrinsic variations in the WD temperature. Schwarz et al (2011) suggested a similar scenario to explain the anti-correlated X-ray and UV variability during the SSS phase of the Galactic nova V458 Vul (see also Ness et al 2009). They drew an interesting parallel to the variability in persistent SSSs which might originate in accretion-rate variations that cause the WD photosphere to expand or shrink (see Reinsch et al 2000;Greiner & Di Stefano 2002).…”
Section: Variabilitymentioning
confidence: 83%
“…2b) might point towards intrinsic variations in the WD temperature. Schwarz et al (2011) suggested a similar scenario to explain the anti-correlated X-ray and UV variability during the SSS phase of the Galactic nova V458 Vul (see also Ness et al 2009). They drew an interesting parallel to the variability in persistent SSSs which might originate in accretion-rate variations that cause the WD photosphere to expand or shrink (see Reinsch et al 2000;Greiner & Di Stefano 2002).…”
Section: Variabilitymentioning
confidence: 83%
“…in V458 Vul (see fig. 6 in Ness et al 2009). Since these novae did not show any persistent oscillations as in V4743 Sgr, our findings are a unique contribution to the discussion about the origin of the early variations in the SSS phase.…”
Section: The Decline On Day 180mentioning
confidence: 99%
“…Before the start of the SSS phase in several novae, emission line spectra had frequently been observed with CCD spectrometers. While their spectral resolution is not high enough to resolve emission lines, the nature as emission line spectra has been established by means of collisional equilibrium models that reproduce these spectra (e.g., Krautter et al 1996;Balman et al 1998;Mukai & Ishida 2001;Orio et al 2001;Ness et al 2009a). Distinct differences to SSe spectra are:…”
Section: Pre-sss and Post-outburst Emission Linesmentioning
confidence: 99%
“…(3) The emission lines in pre-SSS spectra are in most cases too faint for detection in grating spectra; exceptions are V959 Mon (Ness et al 2012b) and symbiotic novae such as RS Oph (Ness et al 2009b). (4) The early hard X-ray component fades with time (Ness et al 2009a), leaving even less potential contributions to SSe spectra.…”
Section: Pre-sss and Post-outburst Emission Linesmentioning
confidence: 99%